Prasa krakowskiej „Solidarności” 1989-2000 (tradycje i rozwój) - Kolasa, Władysław Marek (Acta Universitatis Lodziensis. Folia Librorum, 2013)
The article features traditions and fates of Cracow press related with “Solidarity” movement following 1989. In a period preceding this date, 281 newspapers with roots in the Solidarity movement were published in Cracow and in 1989 a landmark year in Poland only 30 magazines. Over time new newspapers started to appear (18 in 1989, 8 in 1990) but closer analysis shows that majority of them were ephemeral. Among the oldest newspapers only few titles left their mark on a political map, namely: “Bez dekretu” (1984-1989); “Miesięcznik Małopolski” (1983-1989); “Kronika Małopolska” (1982-1989); “Czas Solidarności” (1989); “Hutnik” (1982-1989) and “Promieniści” (1982-1989). Among titles which were issued after June elections a leading part played only one title “Małopolska”/ “Tygodnik Małopolska” (1989-1997) which following the consolidation of the Solidarity movement was transformed into “Tygodnik AWS” (1997-2000). Analysis of its content shows that “Solidarity” press, just as the union, underwent a major change: underground newspapers which embodied defiance and which presented nation’s political aspirations changed into trade newspapers looking for its own identity. Most of these newspapers became later pragmatic bulletins defending workers’ interests or they transformed into party newspapers (“Tygodnik AWS”). Fate of such transformed newspapers were strictly connected with election results and as a result of camp breaking up in 2000, they definitely gone from the market.